IN ORDER TO EXAMINE THE TENSILE STRENGTH OF EN8 STEEL AFTER IT HAS BEEN CRYOGENICALLY TREATED (International Journal of Food and Nutritional Sciences, 2022)
In an effort to achieve more efficient machining at a lower cost, aninvestigation into the tensile strength of EN8 steel that has been cryogenically treated isbeing conducted.In the traditional method of heat treatment, the material is brought to avery high temperature before being cooled by being quenched in oil